Thermal performance of fined plate mini-channel heat sink - Mohamed Ali, Suliman Mohamed; Faris, Waleed Fekry; Ismail, Ahmad Faris; Khan, Sher Afghan (International Organization of Scientific Research ( IOSR ), 2016)
This paper presents fined plate minichannel heat sink numerically under forced convection. Two geometries, flat plate and fined plat heat sinks have been drawn by solidworks, then imported to Starccm+ for simulation. The plate was 45 mm width and 55mm length and the fined heat sink has fins with 3 mm height and 1 mm thickness.Source load 325 W at the bottom of heat sink ad different volumetric flow rate 0.5, 0.75 and 1 liter per minute are used to simulate the microprocessor. The results have shown that fins heat sink has more heat transfer rate, 194.3 watts at 1 liter per minute. Moreover, thermal resistance and base temperature reduced 58 % and 30.7 % compared to flat plate respectively. The results have shown excellent agreement with published experiments.